The RAGE Trial (Radial Arterial Graft in the Elderly)- A Pilot Study - Zaman, Tanveer; Ali, Md Shaukat; Rahman, Shahidur; Begum, Mahfuza; Bhuiyan, Mohammad Ali (Community Based Medical Journal, 2021)
Use of radial artery (RA) as a second arterial conduit in Coronary Artery Bypass Grafting (CABG) is well established and appreciated for its higher long-term patency rate compared to vein grafts. This study tends to investigate if there are any detrimental consequences when it is used in elderly (aged 60 and above) population of Bangladesh. A total of 71 patients who received RA grafts at elective, isolated CABG operation were consecutively enrolled in this study from May 2018 to September 2019. 31 patients were in the Elderly group and 40 patients were in the Non-elderly group. The groups were compared for baseline characteristics and co-morbidities; preoperative techniques, findings, events and procedures; and postoperative outcomes or end-point variables inclusive of local complications related to RA harvesting wound. Elderly and Non-elderly groups had statistically different age (p=0.000) and Society of Thoracic Surgery (STS) Score predicted mortality (p=0.000). Operative techniques, events, findings and procedures were similar. Clinical outcomes were found to be similar with no statistical difference between the groups. Number of deaths also was not statistically different. There were no local complications related to RA harvesting wound in either of the two groups. Harvesting and grafting of radial artery in suitable patients, using meticulous "no-touch" technique and for ideal target coronary artery stenosis is as safe in the elderly patients as in the younger ones. CBMJ 2020 July: Vol. 09 No. 02 P: 08-13